Ultrasound experience complications of the second half of gestation - Pacheco Romero, José (2015)
5,856 scans performed in a specialized ultrasound service was revised, selected 360 cases with complications from the second half of pregnancy. The most frequent pathology was oligoamnios, followed by fetal growth retardation, premature aging and placenta previa. Other complications were large fetus, polyhydramnios and premature detachment of the placenta. With the exception of fetal growth retardation in our diagnostic accuracy was 68.2%, in all cases in which the conditions of the fetus, placenta and amniotic fluid at birth, our diagnosis was always right was recorded. It lacked data on reports of labor in several cases of changes in the volume of amniotic fluid and the placenta premature aging do. The oligamnios often coincided with premature aging of the placenta and fetal growth retardation, but also was found in the prolonged pregnancy and premature rupture of membranes. A study of the various entities submitted regarding how you are seen by the sonographer and the possible reasons for our diagnostic certainty in the revised pathology is discussed, as well as our failures intrauterine fetal growth.